Finite-Time Stability of Neutral Fractional Time-Delay Systems via Generalized Gronwalls Inequality - Pang Denghao; Jiang Wei (Abstract and Applied Analysis)
This paper studies the finite-time stability of neutral fractional time-delay systems. With the generalized Gronwall inequality, sufficient conditions of the finite-time stability are obtained for the particular class of neutral fractional time-delay systems.